CAMKIIγ, HSP70 and HSP90 transcripts are differentially expressed in chronic myeloid leukemia cells from patients with resistant mutated disease - Gonzalez, Mariana Selena (2014)
Patients with chronic myeloid leukemia (CML) can develop disease resistance to tyrosine kinase inhibitor (TKI) therapy, which is mainly attributable to the presence of point mutations in the tyrosine kinase domain of BCR–ABL1. In order to examine suitable markers to monitor treatment efficacy, we investigated transcript expression profiles of genes known to be involved in myeloid cell proliferation, such as CAMKIIγ and KI67, and in protein stability and ultimately cell survival under physiological and stress conditions, such as heat shock proteins HSP70 and HSP90. We studied 101 patients with CML in different stages of disease and with different responses to TKI treatment. The results of quantitative real-time polymerase chain reaction (qPCR) analyses showed that the expression levels of CAMKIIγ, KI67, HSP70 and HSP90 genes were up-regulated at diagnosis, and in cases with signs of treatment resistance both in chronic and advanced phases (accelerated and blastic phases) with respect to chronic phase in remission and healthy donors. When only 56 resistant cases, 31 with mutations (MT) and 25 without mutations (WT), in the BCR–ABL1 tyrosine kinase domain were considered, the transcript expression profile showed an unexpected significant increase in CAMKIIγ and HSP70, and a significant decrease in HSP90 in MT versus WT cases. This differential transcript expression prompted us to design an expression score, log(CAMKIIγ × HSP70/HSP90), which can be used to provide rapid screening to discriminate the presence or absence of mutations in resistant cells and to monitor TKI treatment efficacy in patients with CML.